School Social Workers in the Milieu: Ubuntu as a Social Justice Imperative - Lynn Lim; Johanna C Baez; Meghan Gabriel Pataky; Ellen Wilder; Hester Wilhelmina van Sittert (International Journal of School Social Work, 2022)
Supporting community resilience throughout the milieu, or school community, is a social justice imperative in providing trauma-informed approaches in education. More school social workers need to view their work as a community-level intervention with a trauma-informed approach that includes collaborating with students and staff throughout the building and within the neighboring community. This conceptual article will explore the humanistic concepts of the milieu as a focus of intervention and the South African value of ubuntu, our interconnectedness, through the lens of school social work. The milieu is a humanistic principle in which the community works together to support each other. For school social work, the milieu is not just providing one-on-one counseling in our individual offices, but also working throughout the school building and community by collaborating with teachers, supporting transition times between classes, and spearheading community meetings. Ubuntu is seen as the essence of being human and promoting our interconnectedness, as a person is a person through other people. School social work that promotes ubuntu holds empathy at the forefront and prioritizes connections and supporting others. In South Africa, the ubuntu philosophy has been used to heal national trauma after the Apartheid and many South African schools support ubuntu through their principles within the school community. These concepts work together to support community resilience and need to be a part of key practices in global trauma-informed education. These practices will be explored through school-based case examples across the United States and in South Africa. Lastly, recommendations will be provided for how school social workers can use these practices in their schools.
Keywords: school social work; social justice; trauma-informed; milieu; ubuntu